2021
DOI: 10.2147/ccid.s285564
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of COX-2 Associated with the Depth of Invasion on Acral Melanoma by Increasing TGF-β1

Abstract: Introduction Acral melanoma (AM) has a poor prognosis since it is easily metastatic and resistant to chemo and immunotherapy. Cyclooxygenase-2 (COX-2) is an enzyme that plays a role in the carcinogenesis process. The increased expression of COX-2 has an impact on increasing levels of Myeloid-Derived Suppressor Cell (MDSC), which is a key regulator of immune. The increase in MDSC produces Transforming Growth Factor β1 (TGF-β1), which will suppress Natural Killer (NK) cells and Dendritic Cells (DC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…6 These findings are consistent with the research of Gipsyianti et al, which revealed high COX-2 immunoexpression in acral melanoma; Szlendak et al on colorectal adenocarcinoma; and Liu et al on renal cell carcinoma. 3,20,21 The results of the present show a significant association between COX-2 immunoexpression and the occurrence of metastases in ccRCC (p=0.001) with a POR of 10.28. These results indicate that ccRCC patients with high COX-2 immunoexpression are ten-times as likely to be associated with metastases as ccRCC patients with low COX-2 immunoexpression.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…6 These findings are consistent with the research of Gipsyianti et al, which revealed high COX-2 immunoexpression in acral melanoma; Szlendak et al on colorectal adenocarcinoma; and Liu et al on renal cell carcinoma. 3,20,21 The results of the present show a significant association between COX-2 immunoexpression and the occurrence of metastases in ccRCC (p=0.001) with a POR of 10.28. These results indicate that ccRCC patients with high COX-2 immunoexpression are ten-times as likely to be associated with metastases as ccRCC patients with low COX-2 immunoexpression.…”
Section: Discussionmentioning
confidence: 50%
“…6 These findings are consistent with the research of Gipsyianti et al, which revealed high COX-2 immunoexpression in acral melanoma; Szlendak et al on colorectal adenocarcinoma; and Liu et al on renal cell carcinoma. 3 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…The research was carried out in terms of the role of the zinc finger protein ZNF224 in signaling the TGFβ pathway as a stimulator of the pro-oncogenic function of TGFβ favourable to epithelial-mesenchymal transition [ 9 ]. Moreover, Gipsyianti et al [ 35 ] noted the participation of both TGFβ and cyclooxygenase- 2 (COX-2) in the development of acral melanoma (AM), as well as the depth and invasion of the lesion. The involvement of the TGFβ pathway in the development of melanoma has also been noted by Ren et al [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This develops because PGE2 eliminates the expression of CD127 on the surface of CD8+ T lymphocytes, decreasing their role as immunological surveillance and their capacity to proliferate. 12 TGF-β1, on the other hand, acts as an immunosuppressor by decreasing the activity of CD8+ T cells, NK cells, and dendritic cells. 23 In the end, the number of CD103+ T cells will decrease because the total number of CD8+ T cells is reduced since it is known that only CD8+ T cells express intratumor CD103+ T cells.…”
Section: Discussionmentioning
confidence: 99%